STRATEGIES TO OVERCOME LEARNING LOSS OF ISLAMIC EDUCATION IN THE POST-PANDEMIC ERA - mirza mahbub (Universitas Muhammadiyah Surabaya, 2022)
Online learning is one solution to replace face-to-face learning in current conditions, but online learning cannot replace face-to-face learning, which can develop holistic thinking skills. Therefore, this article aims to find a strategy to overcome learning loss in Islamic education in the pandemic era. This type of research is qualitative field literature research with a descriptive analysis approach. To explore the strategy for overcoming learning loss in Islamic education in the pandemic era. This research used a phenomenology approach. In its characteristics, the phenomenology approach will show an in-depth understanding of the learning loss and its solutions. The analysis techniques are (1) content analysis, (2) Miles and Huberman (data collection, data reduction, data display, and data verification), and (3) data triangulation. The findings in this study are there are strategies to overcome the problem of learning loss, namely Creating a school atmosphere, Innovative learning media, the role of parents in understanding the material, Establishing communication with teachers.